2015
DOI: 10.1093/bja/aev217
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin and pain after total knee arthroplasty: a double-blind, randomized, placebo-controlled, multidose trial †

Abstract: ClinicalTrials.gov: http://www.clinicaltrials.gov/ct2/show/study/NCT01333956.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 29 publications
2
58
2
2
Order By: Relevance
“…A study by YaDeau et al41 found that pregabalin, as a component of a multimodal pain regimen, did not reduce pain, increased sedation, and decreased patient satisfaction. Therefore, pregabalin was found to have no beneficial effect.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
“…A study by YaDeau et al41 found that pregabalin, as a component of a multimodal pain regimen, did not reduce pain, increased sedation, and decreased patient satisfaction. Therefore, pregabalin was found to have no beneficial effect.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
“…Though lower plasma GABA level had a significant independent association with POD [75], a perioperative course of gabapentin produced only a clinically insignificant improvement in analgesia, but was associated with a higher incidence of sedation [76]. Pregabalin had no beneficial effects after total knee arthroplasty, either, but increased drowsiness and confusion [77]. Steroids (methylprednisolon or dexamethasone) did not affect the risk of POD in two large RCTs in cardiac surgery [78,79].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…These studies used a single very small dose of pregabalin (up to 5 mg/kg) given before surgery. However, these trials failed to confer a significant reduction of chronic postsurgical pain [17,18] . When this failure is considered in light of the present results, it may be possible that an effective preemptive analgesia would necessitate the administration of higher doses of pregabalin than the one tried, repeated over several days PRE.…”
Section: Discussionmentioning
confidence: 99%